2020
DOI: 10.3390/ani10030513
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Carcass Composition, Haematology and Immunity of Broilers Supplemented with Sumac Berries (Rhus coriaria L.) and Thyme (Thymus vulgaris)

Abstract: Simple Summary: Widespread use of antibiotics is known to cause resistance in bacteria, yet they are routinely used to improve growth performance in meat chickens. We investigated two medicinal plants, thyme and sumac berries, for their ability to function as an alternative to antibiotics in the diet of broilers. The actual plants or parts of the plants have rarely been fed before as supplements, mostly their extracted oils have been used instead. In our study, they were fed at 1-3% of the diet to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
(42 reference statements)
1
11
0
Order By: Relevance
“…Similarly, FCR was also improved in the treatment groups compared to the control. Reduced feed intake has been reported previously in experiments conducted on broiler fed with these plants (Duru et al 2013) or combination of some other herbal products (Ahmadian et al 2020;Galli et al 2020). The lower feed intake may be due to the unpleasant smell, taste and anti-proteolytic activities.…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, FCR was also improved in the treatment groups compared to the control. Reduced feed intake has been reported previously in experiments conducted on broiler fed with these plants (Duru et al 2013) or combination of some other herbal products (Ahmadian et al 2020;Galli et al 2020). The lower feed intake may be due to the unpleasant smell, taste and anti-proteolytic activities.…”
Section: Discussionmentioning
confidence: 61%
“…Although there were positive effects on production performance in the present study, there were no effects on carcass characteristics measured, which was in line with data reported by Salehimanesh et al and De Souza et al [ 80 , 81 ]. On the contrary, Tayeri et al [ 82 ] showed effects on carcass composition with symbiotic use of probiotics and prebiotics and Ahmadian et al [ 83 ] using thyme essential oil.…”
Section: Discussionmentioning
confidence: 99%
“…Thymol is extracted from the spice oregano, as a medicinal plant essential oil. It has attracted wide attention because of its anti-inflammatory, antioxidant, antibacterial, and antifungal biological activities ( 8 10 ). In recent years, thymol has been attracting the close attention of researchers, as monoterpene alcohol, its antibacterial activity is related to its structure, thymol can overcome the lipid barrier and target the cell membrane of the hydrophobic pathogen, which can be integrated into the lipid layer of the cell membrane and induce its instability.…”
Section: Introductionmentioning
confidence: 99%